TiO2/Pt/TiO2 Sandwich Nanostructures: Towards Alcohol Sensing and UV Irradiation-Assisted Recovery - Rungroj Maolanon; Winadda Wongwiriyapan; Sirapat Pratontep (Journal of Chemistry)
The TiO2/Pt/TiO2 sandwich nanostructures were synthesized by RF magnetron sputtering and demonstrated as an alcohol sensor at room-temperature operation with a fast recovery by UV irradiation. The TiO2/Pt/TiO2 layers on SiO2/Si substrate were confirmed by Auger electron spectroscopy with the interdiffusion of each layer. The TiO2/Pt/TiO2 layers on printed circuit board show the superior sensor response to alcohol in terms of the sensitivity and stability compared to the nonsandwich structure, that is, the only Pt layer or the TiO2/Pt structures. Moreover, the recovery time of the TiO2/Pt/TiO2 was improved by UV irradiation-assisted recovery. The optimum TiO2/Pt/TiO2 with thicknesses of the undermost TiO2 layer, a Pt layer, and the topmost TiO2 layer being 50 nm, 6 nm, and 5 nm, respectively, showed the highest response to ethanol down to 10 ppm. Additionally, TiO2/Pt/TiO2 shows an excellent sensing stability and exhibits different sensing selectivity among ethanol, methanol, and 2-propanol. The sensing mechanism could be attributed to the change of Pt work function during vapor adsorption. The TiO2 layer plays an important role in UV-assisted recovery by photocatalytic activity and the topmost TiO2 acts as protective layer for Pt.